2021
DOI: 10.53986/ibjm.2021.0055
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis on infective endocarditis

Abstract: Introduction: Although infective endocarditis (IE) is rare disease, this disease has importance due to its high morbidity and mortality rates. The exact incidence is not known as it is not a reportable disease. Unlike developed countries, the disease affects the young more than the elderly in developing countries. Most of the time, the diagnosis cannot be made at the first examination and the disease is often overlooked. In order to reduce the mortality and morbidity of this disease, it is important to quickly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It was found that the publications were from 274 different countries. Most of the publications were from the USA, as in previous bibliometric analysis on different topics (Durgun, 2021;Gürler et al, 2021;Köylüoğlu et al, 2021;Küçük et al, 2021;Akyüz et al, 2022;Mızrakçı, 2022). Also, Italy and Greece were in the top 3 countries on thalassemia minor research.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It was found that the publications were from 274 different countries. Most of the publications were from the USA, as in previous bibliometric analysis on different topics (Durgun, 2021;Gürler et al, 2021;Köylüoğlu et al, 2021;Küçük et al, 2021;Akyüz et al, 2022;Mızrakçı, 2022). Also, Italy and Greece were in the top 3 countries on thalassemia minor research.…”
Section: Discussionmentioning
confidence: 94%
“…research productivity. Gaps in study areas can be found and even comparisons of prior studies on a topic (Alkan Çeviker et al, 2021b;Durgun, 2021;Dindar Demiray et al, 2021a;Dindar Demiray et al, 2021b;Gürler et al, 2021;Köylüoğlu et al, 2021;Küçük et al, 2021;Özlü, 2021a;Özlü, 2021b;Mızrakçı, 2022;Akyüz et al ,2022). In bibliometric analysis, Internet databases are commonly used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also provide details on research clusters, current topics of interest, and emerging topic trends. Visualization techniques can be used to analyse and map a variety of databases (Dindar Gürler et al, 2021;Köylüoğlu et al, 2021;Küçük et al, 2021;Mızrakçı et al, 2021;Özlü, 2021;Akyüz et al, 2022;Durgun et al, 2022). In this study both visualization techniques and data analyses were done.…”
Section: Discussionmentioning
confidence: 99%
“…The use of EVLA is not widely reported in pediatric cases, but some reports have been published in recent years (Patel et al, 2017;Bittles et al, 2019). In order to provide a quantitative examination of textual publications, bibliometric methodologies have been utilized (Huffman et al, 2013;Küçük et al, 2021). A bibliometric tool called VOSviewer is used to build relationship networks and visualize data.…”
Section: Introductionmentioning
confidence: 99%